1.2(x-2)-3(4x- 1)= 9( 1-x)
2. 1 1x+64-2x = 100-9x
3. 15-(8-5 times) = 7 times +(4-3 times)
4.3(x-7)-2[9-4(2-x)]=22
5.3/2[2/3( 1/4x- 1)-2]-x = 2
6.2(x-2)+2=x+ 1
7 . 0 . 4(x-0.2)+ 1.5 = 0.7x-0.38
8.30 x- 10( 10-x)= 100
9.4(x+2)=5(x-2)
10. 120-4(x+5)=25
1 1. 15x+863-65x = 54
12. 12.3(x-2)+ 1 = x-(2x- 1)
13. 1 1x+64-2x = 100-9x
14. 14.59+x-25.3 1 = 0
15 . x-48.32+78.5 1 = 80
16.820- 16x=45.5×8
17.(x-6)×7=2x
18.3x+x= 18
19.0.8+3.2=7.2
20. 12.5-3x=6.5
2 1. 1.2(x-0.64)= 0.54
22.x+ 12.5=3.5x
23.8x-22.8= 1.2
24. 1\ 50x+ 10=60
25.2\ 60x-30=20
26.3\ 3^20x+50= 1 10
27.4\ 2x=5x-3
28.5\ 90= 10+x
29.6\ 90+20x=30
30.7\ 69 1+3x=700
3 1 x+5=8
32 3x+5( 138-x) = 540
33 x-5=3
1 2x- 10.3x= 15
2 0.52x-( 1-0.52)x=80
3 x/2+3x/2=7
4 3x+7=32-2x
5 3x+5( 138-x)=540
6 3x-7(x- 1)=3-2(x+3)
7 18x+3x-3 = 18-2(2x- 1)
8 3(20-y)=6y-4(y- 1 1)
9 -(x/4- 1)=5
10 3[4(5y- 1)-8]=6
1 1 2(x-2)+2 = x+ 1
12 2(x-2)-3(4x- 1)= 9( 1-x)
13 x/3 -5 = (5-x)/2
14 2(x+ 1)/3 = 5(x+ 1)/6- 1
15( 1/5)x+ 1 =(2x+ 1)/4